THE FOUNTAIN FITNESS PARK - Revana, Ayu; Hendriana, Hendriana; Widjaja, Stephen; Angkasa, Josef Darmawan (Journal of Business Strategy and Execution, 2013)
In major cities, people started to feel bored with the daily routine activities and also a traffic jam, three aspects of the loss of the consequences of congestion which are: fuel wastage due to the vehicle operating cost 3 Billion IDR, losses due to the time wasted 2.5 Billion IDR, and the health impacts of air pollution 2.8 Billion IDR." the lack of a healthy lifestyle in terms of diet and patterns of daily life will lead to the decreased productivity of a person, now urban society has begun to change their lifestyle towards a healthier keep the body fit to support its. Inspired by the things mentioned above, through this thesis we are interested in creating a new business in which we combine the fitness center with nature concept. The place designed to be natural so visitor feel comfortable exercising, that place we call "THE FOUNTAIN" Fitness Park. We use the calculation so any risks that rise can be managed properly so that we will get profit in relatively short term. One of the easiest ways to prepare a business plan is to create a "frame" or building blocks well integrated. Key activity in this business is we create a sports facility that very unique and profitable in Indonesia. The basic concept is that we offer combines elements of sports and entertainment in one place that nuanced nature. Fountain's Vision is to be the first fitness center in Indonesia with a unique nature concept.